Mengkaji Kembali Konsumsi Umat Sebuah Rekonstruksi Interdisiplier terhadap Gaya Hidup Nabi - Ahmad Sahidah (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2012)
This article analizes the issues of consumtion in Muslim societies and attempts to reconturct the Islamic perspective on comsumption. By referring to the biography of Prophet Muhammad, the write argues that despite the fact that there are religious narratives on the way Muslims should behave in their everyday life; the Muslim perspective of consump- tion should also be discussed critically by utilizing interdisclipnary studies in humanities and social sciences. The writer argues that the utilization of modern social sciences, both religious and secular, in understanding Islamic tradition, will bring to new Muslim interpretation on certain issues such as the theory of production and consumption in Muslim societies. It is believed that the Prophet Muhammad’ life style can be example for Muslim in modern times, as Prophet was very concerned with the issues of public health, cleanliness, and orderliness